The Effect of Counseling on Family Planning Acceptors in Decision Making on Contraceptive Devices during the Postpartum Period - Ernawati; Siti Nurjanah; Nadya Puspita Adriana; Erinda Nur Pratiwi; Arista Apriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Indonesia is one of the developing countries in the world, which is ranked 4th with the largest population in the world. Indonesia has policies to control population growth, including through the Family Planning (KB) program. Family planning is an effort made by humans to intentionally regulate pregnancy in the family not against the laws and morals of Pancasila for the welfare of the family. Through the family planning program there will be control of population growth so that it can increase the level of health and welfare for the family. The current method is a one group pretest posttest design. The population of prospective family planning acceptors at PMB Mira Haryati Bangsalan Teras Boyolali. Data were taken using a family planning counseling questionnaire. The results show that the effect of giving intervention on decision making is Z -4.723, and the effect is significant, which is indicated by ap value of 0.000.